Design and test of superconducting magnet for 200 MeV proton cyclotron. (January 2019) - Du, S.; Zou, C.; Ding, K.; Liu, X.; Chen, Y.; Song, Y.
Highlights: A compact superconducting coil which designed for SC-200 proton cyclotron has been described in this paper. The zero-boiling cryogenic system has been tested. The first powering of the coil has been tested. Abstract: The proton therapy has fulfil many requirements set by the advanced particle therapy for the cancer patients. Based on the compactness and stabilization design guideline, a compact superconducting proton cyclotron project has been launched at Chinese Academy of Sciences (CAS). Superconducting magnet is the most crucial and challenging subsystem for the cyclotron to provide high central magnetic field and average magnetic field to beam extraction. The superconducting coil has been designed and manufactured last year. A cryogenic test platform was set up to verify the coil electrical performance and the superconducting power quench protection system. In this paper, The R&D of the superconducting coil system are outlined in detail, including the coil design and energizing process. The test results are also presented.